نظرية عباس محمود العقاد في تربية المرأة وتحريرها - Saidah, Nur (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
The issue of women is still a serious discourse for discussion, both about the identity,position and role, even to the character and intellect. This article discusses the theoryof education and emancipation of women in view of Abbas Mahmud al-‘Aqqad, anEgyptian thinker, poet, philosopher and journalist scholars in the late - 19th and early20th century. According to Him, women have equal footing with men in education and allsocial roles. But the natural differences between women and men demanding the divisionof different roles, so that the relationship of women and men should be a partnership.Conservative viewsof ‘ Aqqad theory based on the Koran, the Hadith and the researchon the female characters. This theory is in line with structuralist functionalist theory.Structuralist theory gravitate to sociology, while learning functionalist psychologicaltheory, but they have same conclusion, that the relationship of women and men is thepreservation of harmony, not competition. ‘Aqqad’stheory could be a solution to the issueof family crisis and child neglect that often occurs as a result of the division of the maritalpartnership roles are less than ideal.